A Case of Myocardial Infarction in a Fifteen-Year-Old Patient Not Having a History of Cardiac Diseases - S. N. Ivanov; N. V. Kukhtinova (Вопросы современной педиатрии)
Myocardial infarction is an extremely rare disease in paediatrics, yet it has a broad spectrum of causes, including illnesses affecting myocardium, coronary vessels, and a whole spectrum of hereditary diseases. The article describes a case of myocardial infarction in a healthy teenager and analyzes all possible causes of the disease.